Training Acrylic Skills in Empowering Women in the Service of Women Empowerment and Child Protection - Shavira, Vira (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2021)
The training has elements such as training containing the objectives to be achieved, training takes place outside the school system, and training provides knowledge and skills to improve the quality of life. The process of community empowerment through out-of-school education is actually an effort that enables the community with all its empowerment to empower itself. With the center of activity should be in the hands of the people themselves with starting point from the community, carried out by the community and its benefits for the community or in other terms community-based education. The condition of women in Indonesia today is very alarming, women are seen as weak and only considered as someone who is only able to carry out their duties as a housewife. In addition, with the patriaki culture still prevailing in Indonesian society. The state of patriarchal culture directly or indirectly places women in the lower classes after men. Finally what happens is the dichotomy, which is the ruling society and the ruling humans. To free the situation of mastering and being controlled, liberation must be carried out through the process of empowering those who are controlled (empowerment of the powerless). Empowerment or empowerment can be interpreted as providing power or strength to someone because he is considered helpless or the strength that is so small that he can hardly do anything. In Dinas Pemberdayaan Perempuan dan Perlindungan Anak Kabupaten Karawang there are several fields and one of them is a field Peningkatan Kualitas Hidup Perempuan and Keluarga This field has the main task of carrying out part of the duties of the Head of Service in terms of facilitation, coordination, management, guidance and monitoring and evaluation of the implementation of women's empowerment and increasing family security. Therefore effort Dinas Pemberdayaan Perempuan dan Perlindungan anak in empowering women by forming groups named after them PEKKA located in the Desa Mekarjati. PEKKA is is an abbreviation of Perempuan Kepala Keluarga. This study aims to determine and describe the process of acrylic skills training, then what are the supporting and inhibiting factors in training and also how are the results of acrylic skills training in empowering women in Dinas Pemberdayaan Perempuan Dan Perlindungan Anak. This research is a qualitative research with case study method whose data is obtained from interviews and this research was conducted at Dinas Pemberdayaan Perempuan Dan Perlindungan Anak Karawang Based on the results of the analysis and discussion, it can be concluded that the Pelatihan Keterampilan Akrilik Dalam Pemberdayaan Perempuan in the Dinas Pemberdayaan Perempuan Dan Perlindungan Anak Karawang District has been quite successful in providing training to PEKKA members to empower women who have become PEKKA members in Desa Mekarjati Karawang Regency.Keywords: Acrylic Skills Training, Women's Empowerment.